New Palauan-English Dictionary - Josephs, Lewis S. (PALI Language Texts-Micronesia, 1990)
Based on the Palauan-English dictionary by Fr. Edwin G. McManus, S.J. (UH Press, 1977), this revision is designed to be an easily accessible reference for identifying vocabulary items of Palauan, which are often culture bound, semantically rich, and structurally quite complex. Thousands of Palauan entries are new or greatly expanded. Users will benefit from a much wider range of vocabulary, especially in the areas of flora and fauna, Palauan legend, and borrowed words from both English and Japanese. The expanded English-Palauan finder list allows for quick reference to the Palauan equivalents of many English words.